Composite "1.2361 tool steel – Ti – TiO2" structure and its production by resistance welding with subsequent induction heat treatment. (15th December 2018) - Fomin, Aleksandr; Egorov, Ivan; Shchelkunov, Andrey; Fomina, Marina; Koshuro, Vladimir; Rodionov, Igor
Abstract: The composite "1.2361 tool steel – Ti – TiO2 " structure was prepared by resistance welding (RW) with subsequent induction heat treatment (IHT). RW of tool steel with titanium was performed at an electric power in the range of 3.5–4 kW with the pulse duration of 0.25–1.0 s. IHT was performed at the temperatures in the range of 950–1600 °C for 5–60 s for titanium inserts, and the temperature of the steel substrate did not exceed the melting point (about 1370 °C). At the electric power of 3.5 kW with the pulse duration not more than 0.5 s, Fe–Ti transition area of the weld joint with the moderate hardness about 4.0 ± 0.5 GPa (410 ± 50 HV1 ) was formed. According to the results of scanning electron microscopy with energy dispersive X-ray analysis (EDX) and Vickers hardness test, titania coatings with high hardness about 2500 ± 250 HV1 and 950 ± 50 HV5 were formed on titanium surface after IHT at 1500 ± 50 °C for 30 ± 10 s. Preliminary results on the cuttability tests of the experimental replaceable cutting inserts were obtained, according to which the composite "1.2361 tool steel – Ti – TiO2 " structure enabled the fine turning of X40Cr13 steel (43 HRC or 415 HV).